The role of microfinance institutions in poverty reduction in Tanzania: A case study of the National Microfinance Bank in Ngara District council - Ntandu, Omary Musa (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of Masters Degree of Science in Accounting and Finance (MSc A&F) of Mzumbe University.